Fibrinolytic Activation of Plasma by Means of Urokinase in Vitro and in Vivo - Nanninga, L. B; Guest, M. M (Thrombosis and Haemostasis, 1970)
The activation of plasma by urokinase was studied in vitro by measuring the levels of fibrinogen, the anticoagulant split product of fibrinogen and the level of profibrinolysin. It is concluded that normal plasma contains about one CTA unit of plasmakinase, expressed in urokinase equivalents. The level of free fibrinolysin after complete activation of profibrinolysin was estimated to be approximately one-tenth of the initial profibrinolysin concentration. The split product of fibrinogen is present as an intermediate in a consecutive reaction in amounts dependent on the concentration of the activator present.